Close the deal: Mechanisms for the payment of the purchase price in share purchase and sale agreements - Osorio Ishikawa, Kiomi (2022)
The past events that have shaped our world, such as the COVID-19 Pandemic and the different political outcomes, entailed a scenario of major economic uncertainty in the global market that remains, particularly, in our country. Admittedly, mergers and acquisitions of companies (M&A) in Peru have also been heavily affected. However, it is the market agents’ duty to find new strategies to mitigate the economic uncertainty by generating incentives through legal and financial security to the foreign and national investors.Consequently, in this article, the authors have identified the pricing mechanism, employed in Shares Purchase Agreements, as a key element in the recovery and boosting of M&A deals in the Peruvian market driven by uncertainty. Thus, the authors present the pricing mechanisms that have been traditionally used in Shares Purchase Agreements but also introduce the new trends in global pricing mechanisms that have come to stay and fit.